A case-control study of dietary carotene in men with lung cancer and in men with other epithelial cancers. - Harris, R; Key, T; Silcocks, P; Bull, D; Wald, N (1991)
Dietary carotene intake during the year before diagnosis was estimated for 96 men with lung cancer, 75 men with other epithelial cancers, and 97 hospital controls. Relative to those of men in the lowest third of carotene intake (less than 1,683 micrograms/day), the smoking-adjusted odds ratios for men in the middle (1,683-2,698 micrograms/day) and upper (greater than 2,698 micrograms/day) thirds of carotene intake were 0.67 and 0.45, respectively, for lung cancer (one-sided test for trend, p = 0.048) and 0.63 and 0.65, respectively, for other epithelial cancers (one-sided test for trend p = 0.074). The protective effect of estimated dietary carotene intake was considerably stronger than was the effect of total intake of carotene-rich vegetables and fruits (grams per day), providing some evidence that the protective factor is carotene itself rather than another component of vegetables and fruits.